Value-Based Leadership: Turning Success into Significance - Abdul Ghani, Ahmad Bashawir; Kaliappen, Narentheren; Abu Bakar, Hassan; Mohd Mokhtar, Sany Sanuri; Subramaniam, Chandrakantan; Abu Bakar, Alpah; Othman, Shahrina (UiTM Press, 2022)
Malaysia officially implemented its higher education system pivoting on societal development and domestic needs in 1949. Since then, significant enhancements have been made to the system by incorporating more effective pedagogy and andragogy in teaching and learning (T &L). Higher education (HE) continues to evolve and is susceptible to and influenced by international factors such as globalisation, industrialisation, geo-political changes and economic trades. In a move to enhance and make the higher education ecosystem more dynamic and relevant, the Malaysian government decided to establish the Ministry of Higher Education (MOHE) in 2004. However, in 2013, a decision was made to merge both entities, bringing back the Ministry of Higher Education into the fold of the Ministry of Education. The aim was to accelerate transformation and harmonize strategic educational plans between the two educational ministries. However, a reversal was made in 2015 when MOHE was reinstated to satisfy the call for urgent development of human capital. This development did not last long when it was again abolished in 2018 and re-established in 2020.